Association between deficient levels of vitamin D and the occurrence of selected retinal diseases - Aleksandra Żmijewska; Monika Maleszewska; Mateusz Sztybór; Gabriela Nowak; Marcin Kapica; Julia Piątkiewicz; Maria Krzyżanowska; Karol Momot; Mikołaj Wojtas; Karen Głogowska (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: